After the expulsions: the lost German Heimat in memory, monuments and museums - Graaf, Jenny (2014)
This comparative thesis explores how museums and monuments in postwar east and west Germany commemorate the eastern territories that were lost after 1945. I focus on the concept of Heimat which spans aesthetics and politics, psychological and political identity and emerges from a condition of loss, thus it features highly in my attempt to understand the development and current state of memorialisation. The centrality of the notion of Heimat in expellee memorialisation is a field as yet little explored in research on the expulsions, particularly in east Germany. Following chapters on the historical context, Heimat, and cultural memory, Chapter Three discusses monuments erected between 1947 and 1989 by expellees who resettled in West Germany which are used to mourn, replace, reflect on and revere the old Heimat. I compare post-unification west and east German memorials, discussing key differences resulting from the former taboo on expellee commemoration in East Germany. I additionally examine changing sites of memory, memorials that illustrate a shifting integration process and investigate the use of symbolism. Chapter Four considers the interaction between eyewitnesses, historians and curators in the portrayal of history in museums and Heimatstuben at Görlitz, Greifswald, Lüneburg, Regensburg, Molfsee, Gehren, Rendsburg and Altenburg, in addition to the Altvaterturm in Thuringia. Chapter Five discusses the contentious Berlin Stiftung Flucht Vertreibung Versöhnung Centre, first mooted in 1999 by the Bund der Vertriebenen as a Centre against Expulsions. The tension between ‘German victims’ and ‘victims of the Germans’ is a recurring theme in this thesis. My conclusions highlight how memorialisation is framed clearly within the contemporary socio-political context, demonstrate the durability and flexibility of the term Heimat and illustrate the resilience of the regard for the lost territories, not only for expellees; the idea of the German East persists in German cultural memory.